Fly away ladybird. (2nd May 2019) - Hart, Karen
Abstract : In her final article on transient art, Karen Hart finds inspiration from the short life cycles of mini-beasts and the changes of clouds in the sky. Use her ideas to spur children on to set their own creative goals.